ENICOSTEMMA LITTORALE PROTECTS CELL SURFACE ABNORMALITIES DURING DMBA-INDUCED HAMSTER BUCCAL POUCH CARCINOGENESIS - D.RAJASEKARAN; R.KOWSALYA; R.SELVASUNDARAM; S. MANOHARAN (International Journal of Pharma and Bio Sciences, 2015)
Glycoconjugates [protein bound hexose, protein bound hexosamine, total sialic acid and fucose] play a pivotal role in neoplastic transformation if they are abnormally expressed. The protective effect of Enicostemma littorale leaves on cell surface abnormalities was analyzed by measuring the status of the above said glycoconjugates during 7,12-dimethylbenz(a) anthracene (DMBA) induced hamster buccal pouch carcinogenesis. Tumors were developed in the buccal mucosa of hamsters by painting with DMBA thrice a week for 14 weeks. Elevated levels of glycoconjugates were observed in both plasma and tumor tissues of hamsters treated with DMBA alone. Oral administration of Enicostemma littorale leaf extract at a dose of 250 mg / kg bw to hamsters treated with DMBA significantly brought back the levels of glycoconjugates to near normal range. Enicostemma littorale leaves, thus have the potential to prevent the abnormalities in the glycoconjugates status occurring in DMBA induced oral carcinogenesis.